2020
DOI: 10.1186/s13293-020-00332-5
|View full text |Cite
|
Sign up to set email alerts
|

A community-based study of demographics, medical and psychiatric conditions, and gender dysphoria/incongruence treatment in transgender/gender diverse individuals

Abstract: Background Current understanding about health care in the gender diverse population is limited by the lack of community-based, longitudinal data, especially in the USA. We sought to characterize a community-based cohort of transgender individuals including demographics, gender identities, social characteristics, psychiatric and medical conditions, and medical therapy for gender dysphoria/incongruence. Patients and methods We performed a retrospective chart review of gender diverse residents of Olmsted County… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
9
0
3
Order By: Relevance
“…Although there is increasing evidence that non-binary, trans and gender-diverse persons are disproportionately affected by trauma and adverse health outcomes (Brewerton et al, 2022;Newcomb et al, 2020), none of the studies included in our initial literature search that investigated gender beyond the binary (e.g. Hao et al, 2021;James et al, 2020) fulfilled our methodologically demanding inclusion criteria with regards to study design. Future research should adopt more inclusive assessments of sex and gender (Cameron & Stinson, 2019;Logie et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Although there is increasing evidence that non-binary, trans and gender-diverse persons are disproportionately affected by trauma and adverse health outcomes (Brewerton et al, 2022;Newcomb et al, 2020), none of the studies included in our initial literature search that investigated gender beyond the binary (e.g. Hao et al, 2021;James et al, 2020) fulfilled our methodologically demanding inclusion criteria with regards to study design. Future research should adopt more inclusive assessments of sex and gender (Cameron & Stinson, 2019;Logie et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…After that, the interventions administered during the six-month follow-up period of the case were presented together with the literature: Intervention for mental disorder: In studies on gender dysphoria, the prevalence of mental disorders,major depression and anxiety disorders, in particularwas found to be higher than in the general population (Nuttbrock et al, 2010). In a study on gender dysphoria, it was found that young people experience depression and anxiety (James et al, 2020). It has been stated that the history of suicide in transsexual people is 30% or more (Nuttbrock et al, 2010).…”
Section: Nursing Interventions and Discussionmentioning
confidence: 99%
“…El uso de agonistas gnrh con el propósito de suprimir la pubertad endógena y, así evitar el desarrollo de caracteres sexuales secundarias no deseados, es una estrategia relativamente nueva en el enfoque para tratar niños con disforia de género. Iniciada principalmente por un equipo de especialistas en género en los Países Bajos, la supresión de la pubertad es un recurso cada vez más usado en muchas clínicas de género en todo el mundo (22). El objetivo clínico es disminuir la ansiedad que provocan los cambios propios de la pubertad y, dar más tiempo para conocer su propio género (23).…”
Section: La Supresión De La Pubertadunclassified
“…El efecto buscado de aliviar la ansiedad de esos niños se lograría con el apoyo de los profesionales de salud mental y de otras especialidades. De hecho, el apoyo de orientadores y consejeros a quienes sufren esta situación está ampliamente recomendado (31). • La escasa edad del paciente para consentir en un tema que puede afectar al resto de su vida (32).…”
Section: Dilemas En Torno a La Supresión De La Pubertadunclassified